2007
DOI: 10.1159/000108782
|View full text |Cite
|
Sign up to set email alerts
|

RamB Is an Activator of the Pyruvate Dehydrogenase Complex Subunit E1p Gene in <i>Corynebacterium glutamicum</i>

Abstract: In Corynebacterium glutamicum, the transcriptional regulator RamB negatively controls the expression of genes involved in acetate metabolism. Here we show that during growth in media containing glucose and in complex medium without glucose RamB activates expression of the aceE gene, encoding the E1p subunit of the pyruvate dehydrogenase complex. Thus, RamB functions both as repressor and as activator in C. glutamicum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
(13 reference statements)
2
16
0
Order By: Relevance
“…The genes pfkA, fba, and ldhA are not known targets of the carbon regulators AcnR (represses aconitase gene acn [41]), GntR1 and GntR2 (repress gluconate utilization genes gntP, gntK, and gnd and activate ptsG and ptsS [10]), GlxR (represses gntP, gntK, and isocitrate lyase and malate synthase genes aceA and aceB [38,42]), and LldR (represses the Llactate utilization operon cg3226-lldD [23]). RamB was shown to repress its own gene, aceA, aceB, the acetate activation operon pta-ack, and the alcohol dehydrogenase gene adhA and to activate aceE, which encodes subunit E1 of pyruvate dehydrogenase (2,7,24). The occurrence of RamB binding motifs suggests that ptsG, the tricarboxylic acid (TCA) cycle genes gltA and acn, and the phosphoenolpyruvate carboxykinase and malic enzyme genes pck and malE are regulated by RamB (3).…”
Section: Discussionmentioning
confidence: 99%
“…The genes pfkA, fba, and ldhA are not known targets of the carbon regulators AcnR (represses aconitase gene acn [41]), GntR1 and GntR2 (repress gluconate utilization genes gntP, gntK, and gnd and activate ptsG and ptsS [10]), GlxR (represses gntP, gntK, and isocitrate lyase and malate synthase genes aceA and aceB [38,42]), and LldR (represses the Llactate utilization operon cg3226-lldD [23]). RamB was shown to repress its own gene, aceA, aceB, the acetate activation operon pta-ack, and the alcohol dehydrogenase gene adhA and to activate aceE, which encodes subunit E1 of pyruvate dehydrogenase (2,7,24). The occurrence of RamB binding motifs suggests that ptsG, the tricarboxylic acid (TCA) cycle genes gltA and acn, and the phosphoenolpyruvate carboxykinase and malic enzyme genes pck and malE are regulated by RamB (3).…”
Section: Discussionmentioning
confidence: 99%
“…RamA additionally controls the ramB gene , the gltA gene, the acn gene and the sdhCAB operon, encoding the TCA cycle enzymes aconitase and succinate dehydrogenase Bussmann et al, 2009;Van Ooyen et al, 2010), the gapA gene, encoding glyceraldehyde-3-phosphate dehydrogenase (Toyoda et al, 2009a), the surface-layer protein gene cspB (Hansmeier et al, 2006) and the resuscitation promoting factor 2 gene rpf2 . RamB additionally controls the aceE gene, encoding E1p subunit of the pyruvate dehydrogenase complex (Blombach et al, 2009). From all these results it can be concluded that both RamA and RamB have wide significance as transcriptional regulators in C. glutamicum and play a major role in coordination of its metabolism.…”
Section: Introductionmentioning
confidence: 90%
“…These current and previous findings suggest that, besides basal upregulation by RamA, gapA expression is enhanced in the presence of glucose by inactivating SugR and activating GlxR with sugar metabolites and cAMP, respectively. While pfk is negatively regulated by SugR and RamA (4,27), aceE is positively controlled by RamB, a repressor of acetate utilization genes, under nutrient-rich conditions (10). The binding sites of these regulators in the promoter regions of gapA, pfk, and aceE do not overlap the GlxR-binding sites, eliminating the possibility that the mutations in the GlxR-binding sites affect binding of these regulators.…”
Section: Vol 193 2011mentioning
confidence: 99%